N/O co-enriched graphene hydrogels as high-performance electrodes for aqueous symmetric supercapacitors. Issue 32 (1st June 2021) - Zhang, Yong; Wei, Liang; Liu, Xijun; Ma, Wenhui; Wang, Jiankai; Fan, Shan
Abstract : N/O co-enriched graphene hydrogel based supercapacitors were assembled. Owing to the synergistic effect between the heteroatoms (N, O), 3D porous structures and high specific surface area, they present excellent electrochemical properties. Abstract : In this study, an easy one-pot hydrothermal strategy was used to prepare N/O co-enriched graphene hydrogels (NOGHs) using graphene oxide (GO) solution and n -propylamine as a reactant. The n -propylamine can be used not only as a reductant, nitrogen dopant and structure regulator, but also as a spacer to inhibit the agglomeration of graphene sheets. Benefiting from the synergistic effect between the heteroatoms (N, O), 3D porous structures and high specific surface area, the as-prepared NOGH samples present excellent electrochemical properties. Remarkably, the NOGH-140 based binder-free symmetric supercapacitor shows a high specific capacitance of 268.1 F g −1 at the current density of 0.3 A g −1 and retains 222.5 F g −1 (82.9% of its initial value) at 10.0 A g −1 in 6 M KOH electrolyte. Furthermore, the assembled device also displays a notable energy density (9.3 W h kg −1 ) and outstanding cycling performance (1.8% increase of its initial specific capacitance after 10 000 cycles at 10 A g −1 ). The simple preparation method and excellent electrochemical properties indicate that NOGHs can be used as electrode materials for commercial supercapacitors.